Efficacy of the Whole-Body Cryotherapy as Add-on Therapy to Pharmacological Treatment of Depression—A Randomized Controlled Trial - Rymaszewska, Joanna; Lion, Katarzyna M.; Pawlik-Sobecka, Lilla; Pawłowski, Tomasz; Szcześniak, Dorota; Trypka, Elżbieta; Rymaszewska, Julia E.; Zabłocka, Agnieszka; Stanczykiewicz, Bartlomiej (Frontiers in Psychiatry, 2020)
Introduction: Accumulating evidence indicates the effectiveness of cryogenic temperature interventions in rheumatoid arthritis, ankylosing spondylitis, fibromyalgia, multiple sclerosis, and chronic low back pain. The application of whole-body cryotherapy (WBC) in psychiatric aspects of medicine was also noted. Nevertheless, the exact mechanisms explaining the beneficial effect of WBC on mood disorders remain unclear. The study aimed to assess the efficacy of repetitive short exposure to extremely low temperatures (WBC) on mood, quality of life as well as on biochemical measures among people diagnosed with depressive episode undergoing pharmacological treatment. Materials and Methods: Prospective randomized, double-blind sham-controlled protocol was used. The study enrolled 92 medically stable adults (aged 20-73 years) with a diagnosis of a depressive episode. The participants were randomly allocated and exposed to 10 whole-body cryotherapy sessions ( -110°C till -160°C (the experimental group; EG) or to low, but not cryogenic temperatures -50°C (the control group; CG). Thirty participants in the EG and 26 in CG completed the whole study. The primary outcome measures were depressive symptoms evaluated with the Beck Depression Inventory-II (BDI-II) as well as the Hamilton Depression Rating Scale (HAM-D 17). The quality of life, quality of sexual life, acceptance of the disease and self-reported mood, vitality, and sleep quality were assessed as secondary outcome measures. The study was registered at ACTRN (ACTRN12619001600134). Results: The results show evidence for a statistically significant difference in the clinical assessment of depressive symptoms according to HAM-D 17 scale (T4 by group interaction p=0.02), BDI-II (T2 time by group interaction p=0.01), cognitive-affective BDI dimension (T4 by group interaction p=0.00) and somatic BDI dimension (T4 by group interaction p=0.028). Significant improvement was also noticed in life quality (p<0.05), self-assessed mood (p=0.035), and disease acceptance (p=0.007). There were no statistically significant changes related to sexual satisfaction, self-assessed vitality, and sleep (p>0.05). Conclusions: Whole-body cryotherapy is a useful method to improve standard pharmacological treatment. The WBC intervention reduces mental health deterioration, especially in mood disorders, such as depression, and can be beneficial for well-being and quality of life.